Safeguards, financing, and employment in Chinese infrastructure projects in Africa: the case of Ghana’s Bui Dam - Kirchherr, J; Disselhoff, T; Charles, K (Practical Action Publishing, 2016)
Chinese players are now Africa’s key partner for its infrastructure sector (including water supply projects), providing approximately two-thirds of investments since 2007. The social impacts of these engagements during the construction phase are mostly portrayed in an alarmist tone within the popular press. Meanwhile, scholarly literature investigating them remains scarce. We draw on the Bui Dam, a major dam in Ghana, financed by China Exim Bank (CEB), the largest financier of infrastructure in Africa, and constructed by Sinohydro, the largest dam developer worldwide, as a case study to explore social impacts of Chinese engagements in the African water sector. We particularly examine social safeguards policies from the perspective of Chinese players, the financing modalities, and the dam’s impacts on the local labour market. We find that social safeguards policies were not within the responsibility of Sinohydro. Furthermore, financing modalities were largely favourable from a Ghanaian perspective, comparable to World Bank conditions, partly due to the successful negotiations (from the Ghanaian standpoint) during the planning and design phase of the project. Most likely, the project would not have been implemented if CEB had not stepped in to provide funding. Lastly, we find that most workers employed during construction were Ghanaian, paid significantly above the country’s minimum wage. Nevertheless, working conditions overall were questionable. This case study highlights how Chinese engagement in construction of water infrastructure may help develop projects otherwise stuck in the planning and design phase. However, labour conditions during the construction phase of these projects need to be carefully managed.